[Re(η6‐C6H5‐benzimidazole)2]+ and Derivatives as Dye Mimics; Synthesis, UV Absorption Studies and DFT Calculations. Issue 25 (28th May 2021) - Gotzmann, Carla; Blacque, Olivier; Fox, Thomas; Alberto, Roger
Abstract: Functionalizations of highly oxidation and hydrolysis stable mono‐cationic rhenium bis‐arene complexes [Re(η 6 ‐C6 H6 )2 ] + are of great interest. We directly built up structural features of the well‐known Hoechst Dye on the coordinated arenes as a model for prospective DNA minor groove binding studies. Extensions of the aromatic bis‐arene unit with functionalized and derivatized benzimidazole moieties resulted in a deep orange colour of the complexes, showing UV/Vis absorption spectra with multiple transition maxima. These have been assigned with support of DFT calculations to gain information about their charge transfer natures. The different transitions of the complexes, which are either intra‐ligand, ligand‐to‐ligand or metal‐to‐ligand charge transitions, were additionally compared and discussed with the spectra of the corresponding free ligands. Abstract : Mono‐ and di‐substituted positive‐charged Rhenium‐(η 6 ‐arene) complexes with different functionalized and derivatized benzimidazole units have been synthesized and characterized. UV/Vis studies assisted by DFT calculations give deeper insights into the nature of the absorptions of the complexes.